Lower Hybrid Drift Waves and Electromagnetic Electron Space‐Phase Holes Associated With Dipolarization Fronts and Field‐Aligned Currents Observed by the Magnetospheric Multiscale Mission During a Substorm. Issue 12 (21st December 2017) - Le Contel, O.; Nakamura, R.; Breuillard, H.; Argall, M. R.; Graham, D. B.; Fischer, D.; Retinò, A.; Berthomier, M.; Pottelette, R.; Mirioni, L.; Chust, T.; Wilder, F. D.; et al.
Abstract: We analyze two ion scale dipolarization fronts associated with field‐aligned currents detected by the Magnetospheric Multiscale mission during a large substorm on 10 August 2016. The first event corresponds to a fast dawnward flow with an antiparallel current and could be generated by the wake of a previous fast earthward flow. It is associated with intense lower hybrid drift waves detected at the front and propagating dawnward with a perpendicular phase speed close to the electric drift and the ion thermal velocity. The second event corresponds to a flow reversal: from southwward/dawnward to northward/duskward associated with a parallel current consistent with a brief expansion of the plasma sheet before the front crossing and with a smaller lower hybrid drift wave activity. Electromagnetic electron phase‐space holes are detected near these low‐frequency drift waves during both events. The drift waves could accelerate electrons parallel to the magnetic field and produce the parallel electron drift needed to generate the electron holes. Yet we cannot rule out the possibility that the drift waves are produced by the antiparallel current associated with the fast flows, leaving the source for the electron holes unexplained. Key Points: Dipolarization fronts associated with field‐aligned currents are observed at the plasma sheet edge with a few ion inertial length scale Intense lower hybrid drift waves are detected at the front and can accelerate electrons parallel toB Electromagnetic electron phase‐space holes are detected near the lower hybrid drift waves and could be a latter by‐product of these